Single-Switch Soft-Switched High Voltage Gain Converter With Low Voltage Stress and Continuous Input Current - Mohammad Reza Gholami; Siamak Khalili; Hosein Farzanehfard; Ehsan Adib; Hani Vahedi (IEEE Open Journal of Power Electronics)
This paper introduces a soft-switched high step-up converter applicable to photovoltaic systems. In the proposed topology, to further improve the voltage gain and reduce the components voltage stress, coupled inductors and voltage multiplier cell (VMC) techniques are integrated with the conventional boost converter. Hence, it addresses challenges in traditional boost converter when operating at near unity duty cycle and enables it to utilize high-quality components that lead to decreased conduction losses in high-output voltage applications. Furthermore, the converter achieves soft switching operation by incorporating a lossless snubber cell, which consists of just two diodes and requires no additional switches and magnetic cores. These features contribute to enhancing the converter efficiency. Notably, the energy stored in the snubber circuit is effectively recovered to the output without any circulating current, making it a beneficial characteristic among the lossless snubber structures. The proposed topology also offers a common ground between the input and output terminals, as well as the switch which simplifies the converter control circuit. Additionally, it maintains continuous input current, which makes the proposed converter more suitable for photovoltaic system applications. To validate the converter benefits, a 150 W laboratory prototype converter is implemented.